Phenolic profiles, antioxidant activities and cytoprotective effects of different phenolic fractions from oil palm (Elaeis guineensis Jacq.) fruits treated by ultra-high pressure. (1st August 2019) - Zhou, Jiexin; Ma, Yanli; Jia, Yijia; Pang, Mingjie; Cheng, Guiguang; Cai, Shengbao
Highlights: Ultra-high pressure (UHP) affected phenolics and bioactivities of oil palm fruits. UHP remarkably increased bioaccessibility of different phenolic fractions (DPFs). UHP significantly enhanced antioxidant and cytoprotective activities of DPFs. UHP dramatically upgraded the inhibitory effects of DPFs on intracellular ROS. Abstract: The present work investigated the phenolic profiles, antioxidant activities, and cytoprotective effects of the free, esterified, and insoluble-bound phenolic fractions from oil palm fruits treated under ultra-high pressure (UHP). Results showed that UHP treatment significantly increased the total phenolic and flavonoid contents of all three phenolic fractions ( p  < 0.05). A total of 11 and 12 phenolic compounds were detected and quantified in non-treated and UHP-treated fruits, with caffeic acid having the highest concentration in insoluble-bound phenolic fractions with 8.68 and 11.27 mg/g of dry extract, respectively. The antioxidant activities, intracellular reactive oxygen species inhibition, and cytoprotective effects of all three phenolic fractions were dramatically enhanced after UHP pretreatment ( p  < 0.05). Therefore, UHP-treated oil palm fruits with increased bioactivities could be used in functional food or the nutraceutical industry to enhance their applications and economic value.